PENERAPAN SANKSI ADAT PADA LARANGAN PERKAWINAN EKSOGAMI DI DESA ADAT TENGANAN PEGRINGSINGAN, KECAMATAN MANGGIS, KABUPATEN KARANGASEM, PROVINSI BALI - Luh Indri Prasetyarini; Ni Komang Sutrisni (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
Customary sanctions are an attempt to neutralize violations that occur as a result of customary violations. To determine the application of customary sanctions to exogamous marriages, it can be seen from the regulation of customary sanctions on the prohibition of exogamous marriages and also to see the mechanism for the application of customary sanctions which is seen from the planned implementation based on the reference of norms to achieve its goals. In addition, the application of customary sanctions is inseparable from the factors that influence it, both supporting factors and inhibiting factors. The type of research used is empirical legal research, namely research that conducts observations or case studies in the form of community legal behavior in this case in the Tenganan Pegringsingan Traditional Village, Manggis District, Karangasem Regency. The type of approach used is a factual approach and a sociological approach that looks at the symptoms and reality of the application of customary sanctions on the prohibition of exogamous marriages in the Tenganan Pegringsingan Traditional Village. The legal materials in this study were collected through observation and interviews with the relevant informants.